Freedom of navigation and the law of the sea : warships, states, and the use of force - Moore, Cameron (Cameron Alastair) (Oxon Routledge, 2021)
"There has been a recent increase in clashes between warships asserting rights to navigate and states asserting sovereignty over coastal waters. This book argues for a set of rules which respect the rights of coastal states to protect their sovereignty, and of warships to navigate lawfully, whilst also outlining the limits of each The book addresses the issue of the clash between warships and states in four parts. The first part considers the general principles applying to use of force in the law of the sea and the law of national self-defence. The second part focuses on the right of coastal states to use force to prevent passage of warships which threatens their sovereignty, with particular reference to the specific maritime zones. The third part explores the law of the sea and the international law on the use of force by warships to ensure passage or to defend themselves. The fourth part assesses the extent to which the law of armed conflict may be applicable or useful in relation to these issues. The conclusion draws together a set of rules which take account of both contemporary and historical events, and seeks to balance the competing interests at stake. Providing a concise overview of the enduring issue of freedom of navigation, this book will appeal to anyone studying International Law, the Law of the Sea, Security Studies and International Relations. It will also be of interest to naval, coast guard and military officers, as well as government legal advisors"--
General principles on the use of force and their application at sea -- Unit and collective self defence -- Proportionality and the threshold of armed conflict -- Territorial and internal waters -- Straits and archipelagos -- International waters.
Includes bibliographical references and index.
Keywords: War, Maritime (International law); Self-defense (International law); Warships -- Law and legislation; Contiguous zones (Law of the sea); Maritime boundaries; Freedom of the seas; Mare clausum; Navigation